Inspection cost minimization by optimizing the number of inspectors in apparel manufacturing - Ahmad, Shibbir; Kamruzzaman, M. (Universitas Ahmad Dahlan, 2025)
Apparel manufacturing organizations aim to minimize costs, including inspection costs, but there is a research gap in optimizing the number of inspectors without compromising quality. This study focuses on reducing inspection costs by determining the minimum number of inspectors required. A mathematical model has been developed to calculate inspection costs based on the standard minute value and cost per minute. Additionally, a linear programming (LP) model is introduced to optimize the number of inspectors based on cost and inspection volume while considering their capacity and skill levels. Data from large, medium, and small-scale factories reveal that 30%–35% of inspectors exceed the standard requirement due to a lack of awareness among quality managers regarding inspection capacity, skills, and targets. Large-scale companies employ 25% more inspectors for operational flexibility, while medium and small-scale factories exceed standard requirements by 30% and 35%, respectively, to meet inspection demands. This study proposes an inspection cost reduction tool using LP to determine the optimal number of low-, medium-, and high-skilled inspectors per line for a given production target. Findings suggest that implementing this model can reduce the number of inspectors by 30%, leading to significant inspection cost savings without compromising quality.